Implementasi Prosedur Pengajuan Kredit Umum Pedesaan Pada Bank Rakyat Indonesia Unit Cijeruk - Lutfiah, El Syifa; Suharmiati, Suharmiati; Roestiono, Harry; Effendy, Marwan (Program Vokasi dan LPPM IBI Kesatuan, 2023)
Procedures for applying for KUPEDES at the Operational Work Unit of BRI Bank Cijeruk Unit. Is one of the processes of providing small loans to community groups that have MSMEs with very easy requirements and a very fast process. With the hope that the debtor/borrower can increase his business to be even more developed. For this reason, this discussion aims to find out the procedure for submitting KUPEDES to PT. Bank Rakyat Indonesia Cijeruk Unit. By forming a formulation of the problem regarding service requirements for credit applications, procedures for submitting KUPEDES, obstacles and how to overcome these obstacles. The results of the discussion show that the bank's intermediation function has been carried out properly, which is reflected in the amount of credit that has been distributed to the people of Bogor Regency, especially the Caringin and Cijeruk Districts. PT. Bank Rakyat Indonesia Cijeruk Unit continues to increase the growth of Rural General Credit by conducting promotions through socialization carried out by marketing. Keywords: credit, credit procedures.